Penentuan Kadar Vitamin C dan Aktivitas Antioksidan Buah Carica (Vasconcellea cundinamarcensis) Wonosobo - Hery Muhamad Ansory; Rinda Binugraheni; Argo Khoirul Anas (Fakultas Farmasi Universitas Setia Budi, 2016)
The content of vitamin C information in carica fruit is very important because it can improvethe marketability of this fruit. The potential of Carica fruit as antioxidants agent hasn’t beenstudied by the researchers. It’s made Carica fruit are interesting to be studied, so theresearchers conducted this study to determine the vitamin C contain and the antioxidant activityof Carica fruit that grows in Wonosobo.This study was started by the preparation of the Carica fruit to obatined Carica fruitsolution. So that the total content of organic acids, ascorbic acid, and antioxidant activity ofCarica fruit solution could be analyzed. The organic acid content analysis of Carica fruit solutionwas performed by alkalimetric method. The ascorbic acid content analyses were performed byUV-Vis Spectrophotometry, and analysis of antioxidant activity were performed with DPPHmethod.The organic acids total concentration of Carica fruit solution was equal to 0,4 N. Theascorbic acid concentration of Carica fruit solution was 1560 ppm and The C50 value of Caricafruit obtained from sample solution by 118x dilution or equivalent to 17 gram of Carica fruit.